Condition of Hard Corals and Quality of The Turbid Waters in Spermonde Islands (Case Studies in Kayangan Island, Samalona Island and Kodingareng Keke Island). Issue 1 (November 2021) - Parenden, D; Jompa, J; Rani, C
Abstract: Coral reefs in Spermonde waters have experienced degradation as a result of the increasing turbidity in these waters. This research was conducted on Kayangan Island, Samalona Island and Kodingareng Keke Island, Spermonde Islands, Makassar City. The purpose of this study was to determine the percentage of coral cover, types and the how much the turbidity of the waters influence the coral. The researcher measured the coral cover using Underwater Photo Transect and processed the data using CPCe software. The levels of turbidity were taken at three locations and examined in the laboratory and the other parameters were measured on site. The correlation between turbidity and coral cover was analysed by regression analysis method. Based on the regression results, the turbidity level has a negative effect on coral cover. The level of turbidity is higher on Kayangan Island with 0.89 NTU with a cover percentage of 4.95 %, Temperature of 30°C, Salinity of 30 ppm, DO of 5.44 mg/l, pH 7.8 and the species found were Porites and Faviidae . Samalona Island is 0.43 NTU with a percentage of coral cover of 14.08 %, Temperature of 30°C, Salinity of 30 ppm, DO of 5.44 mg/l, pH of 7.7 and the most common types are Acropora and Fungiidae . Kodingareng Keke Island has a turbidity value of 0.32 NTU, Temperature of 29°C, Salinity of 30 ppm, DO of 6.08 mg/l, pH 7.3 and the most common coral species, Fungiidae . Higher levels of turbidity in Kayangan Island will result in the death of certain coral species (unable to adapt) and will also have an impact on the percentage of hard coral cover.